2000
DOI: 10.1097/00000542-200004000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Direct Coronary Vasomotor Effects of Sevoflurane and Desflurane in In Situ  Canine Hearts

Abstract: Sevoflurane and desflurane have comparable coronary vasodilative effects in in situ canine hearts. The KATP channels play a prominent role in these effects. When compared with data obtained previously in the same model, the coronary vasodilative effects of sevoflurane and desflurane are similar to those of enflurane and halothane but considerably smaller than that of isoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…However, decreases in myocardial oxygen extraction have been reported and hint at possible metabolic modulation. The latter finding appears to be in line with the results presented in Figure , where HR is a poor parameter to explain the observed metabolite ratios ( R 2 L2B, low Iso = 0.064, R 2 L2B, high Iso = 0.125).…”
Section: Discussionmentioning
confidence: 99%
“…However, decreases in myocardial oxygen extraction have been reported and hint at possible metabolic modulation. The latter finding appears to be in line with the results presented in Figure , where HR is a poor parameter to explain the observed metabolite ratios ( R 2 L2B, low Iso = 0.064, R 2 L2B, high Iso = 0.125).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the findings from this study and those from the afore mentioned two studies could be attributed to an ineffective anesthetic level during operations. Furthermore, certain studies have emphasized that the increase in respiratory rate may be caused by the increase in the amount of pCO 2 resulting from the induction of the central and peripheral chemoreceptors [8,18,24,29,42].…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane has been reported to cause respiratory depression depending on dosage,and in the general anesthesia with spontaneous respiration, an increase in the amount of CO 2 in the blood and a decrease in arterial pH occur [8,18,24,29,42]. In this study, the decrease in the pH level of the isoflurane group during administration of anesthesia at the 15th (P < 0.01), 30th (P < 0.001), 45th (P < 0.001), and 60th (P < 0.001) min compared to the baseline value was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane is a frequently used volatile anaesthetic with coronary vasodilating properties [11,12]. Experimental studies showed preservation of myocardial perfusion during sevoflurane anaesthesia if perfusion pressure was maintained [13-15].…”
Section: Introductionmentioning
confidence: 99%